ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PADI SAWAH DI KECAMATAN AESESA KABUPATEN NAGEKEO PADA TAHUN 2013-2017 - Renggo, Markus; Sagajoka, Estherlina; Luciany, Yohanes Paulus (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
The purpose of this study was to determine the effect of rice harvest area, human resources and rainfall on lowland rice productivity and determine the factors that most influence lowland rice productivity. The data used are quantitative and qualitative data sourced from lowland rice productivity data, harvested area data, human resource data and rainfall data taken from BPS Kabupaten Ende and other relevant agencies, within the last five years. The results of his research were three factors, namely harvested area, human resources and rainfall, all of which did not significantly influence the productivity of lowland rice. Of the three independent variables, namely the rice field harvest area variable, the Human Resources variable and the rainfall variable, it can be seen from the coefficient numbers which are more influential on the productivity of lowland rice, namely the harvest area variable and the Human Resources variable which are positive, namely the coefficient of harvested area is 70.451 and the coefficient of Human Resources is 1.671, while the rainfall variable is negative, namely -160.985. From the results of this study, the local government wants to increase the participation of extension workers to the farming community so that their business spirit and creativity are continuously fostered. It is hoped that lowland rice farmers try as often as possible to get direction or socialization from the local government to improve Human Resources or knowledge.